2022
DOI: 10.1088/1361-6595/ac8289
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact cross-sections of tetraethyl silicate

Abstract: The understanding of electron interactions with molecules in plasma is of vital importance from academic and technological point of view. The reliable electron collision data is required to model the electron and ion components of low-temperature and non-equilibrium plasmas. Various electron impact cross-sections like the differential, integral, momentum transfer, partial and total ionizations are reported for tetraethyl silicate (TEOS), a plasma relevant molecule in the energy range between ionization thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…The complex plasma formation mechanism during the interaction of a high-energy pulsed laser with metal materials has been extensively investigated by scholars. Luthra et al 1 reported various electron impact cross sections, modified the binary encounter Bethe model, and validated the efficacy of the modified model in computing the partial ionization cross sections. Hoffmeister et al 2 considered the photoionization generated in a system composed of two atoms of different species by a laser field and showed that when the intensity of the laser field is increased, the photoionization process can acquire qualitatively new features in terms of the time evolution and electron emission spectra.…”
Section: Introductionmentioning
confidence: 98%
“…The complex plasma formation mechanism during the interaction of a high-energy pulsed laser with metal materials has been extensively investigated by scholars. Luthra et al 1 reported various electron impact cross sections, modified the binary encounter Bethe model, and validated the efficacy of the modified model in computing the partial ionization cross sections. Hoffmeister et al 2 considered the photoionization generated in a system composed of two atoms of different species by a laser field and showed that when the intensity of the laser field is increased, the photoionization process can acquire qualitatively new features in terms of the time evolution and electron emission spectra.…”
Section: Introductionmentioning
confidence: 98%